Role of SIRT1-mediated mitochondrial and Akt pathways in glioblastoma cell death induced by Cotinus coggygria flavonoid nanoliposomes [Retraction] - Wang G; Wang J; To T; Zhao HF; Wang J; Hong-Ming T (International Journal of Nanomedicine)
Wang G, Wang J, To T, Zhao HF, Wang J, Hong-Ming T. Int J Nanomedicine. 2015;10(1):5005–5023. We, the Editor and Publisher of International Journal of Nanomedicine, have retracted the published article. Following publication, concerns were raised by a third-party regarding potential duplication in Figures 1C and 3C, 3D, and 3E. Upon investigation by the journal, additional concerns were identified with regards to the western blots in this article. When approached for an explanation, the authors explained that given the length of time elapsed since publication, they were unable to provide the original images for Figures 1C, 3C, 3D, 3E and the Western blot data, including the molecular weight markers. As a result, the concerns remain unaddressed. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in the publication has been informed. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted articles will remain online to maintain the scholarly record, but they will be digitally watermarked on each page as ‘Retracted’.